Reliability and validity of the Chinese version of the Walsh Family Resilience Questionnaire among community-dwelling disabled elderly individuals (WFRQ-CE) - Zhang, Xiangchun; Wang, Anni; Guan, Tingyu; Kuang, Yi; Zhang, Yuyi; Wu, Fangqi (Frontiers in Psychology, 2023)
Objective: To test the reliability and validity of the Chinese version of the Walsh Family Resilience Questionnaire among community-dwelling disabled elderly individuals (WFRQ-CE). Methods: Convenience sampling was used to select 566 dyads of disabled elderly individuals and their caregivers. The Walsh Family Resilience Questionnaire Chinese Version (WFRQ-C) was tested among elderly individuals. The Family Care Capacity Scale for Elderly Patients (FCCSE) was used as a concurrent validation tool for the caregivers, and the Psychological Resilience Scale (CD-RISC-10) and the Social Support Assessment (SSRS-10) were used as concurrent validation tools for both the elderly individuals and the caregivers. Results: Exploratory factor analysis revealed 4 common factors – “Family belief,” “Organization and problem solving,” “Family communication,” and “Utilization of external resources” – with a cumulative variance contribution rate of 56.94%. Confirmatory factor analysis yielded the following fit indices: chi-square/freedom degree (χ2/df) = 2.007, Tucker‒Lewis index (TLI) = 0.900, incremental fit index (IFI) = 0.917, comparative fit index (CFI) = 0.916, parsimony goodness-of-fit index (PGFI) = 0.681, and root-mean-square error of approximation (RMSEA) = 0.060. The concurrent scales were significantly correlated with the WFRQ-C total score and the scores for each factor (r values between 0.23 and 0.60, P<0.01). The Cronbach's alpha coefficient was 0.93 for the WFRQ-CE and 0.87, 0.83, 0.89 and 0.65 for the four factors; the retest reliability was 0.96 for the total scale and 0.95, 0.92, 0.92 and 0.95 for the four factors; the split-half reliability was 0.85 for the total scale and 0.81, 0.78, 0.79 and 0.68 for the four factors. Conclusion: The WFRQ-CE has good reliability and validity among community-dwelling disabled elderly individuals and can be used to evaluate the level of family resilience.